MODERNİTE VE GELENEK ARASINDA HASAN EL-BENNÂ'NIN FIKIH DÜŞÜNCESİ - YARALI, FATMA (Fırat Üniveristesi, 2025)
Hasan el-Bennâ (1906-1949), tüm dünya ve özellikle İslam alemi için içtimai, kültürel ve hukuki alanlar başta olmak üzere her alanda gerçekleşen bir geçiş, arayış ve devrim döneminde yaşamıştır. Bu dönemde Müslümanların yaşadıkları buhranlara karşı birtakım çözüm önerilerinde bulunan Hasan el-Bennâ'nın fıkhi ve usuli görüşlerinin tespiti dönemin irdelenmesi açısından önemlidir. Bir ilim ve hareket adamı olarak Bennâ'nın eserleri incelendiğinde, onun fıkıh anlayışının selef-i sâlihîn düşüncesi ekseninde olduğu, ama aynı zamanda bu düşünceyi yenilikçi ve ıslahatçı bir yaklaşımla da desteklediği görülmektedir. Başta icmali deliller olmak üzere usuli kavramları açıklarken ümmetin birliğini sağlama amacı üzerinden görüşlerini belirtmesi, onun fıkıh düşüncesini inşa ederken usulde farklı bakış açıları geliştirdiğini göstermektedir. Özellikle Fıkıh Risâlesi adlı eserinde onun daha çok Kitâb ve Sünnete odaklandığı söylenebilir. Çünkü ona göre Batı'nın dayattığı modern ulusal devlet anlayışına karşılık farklı ırk ve mezheplerden Müslümanların birlik olabilmesi, bu iki asli delilin daha işlevsel hale gelmesine bağlıdır. Bennâ, kurumsal olarak Müslümanların anayasal sisteme geçmesinde Kur'an'ın etkin rol oynayabileceğini savunmuştur. Kur'ân'ın deliller hiyerarşisindeki konumu ona göre doğrudur ancak bu delil uygulanabilirlik bakımından tıpkı bir anayasa gibi toplumun her alanında işlevsel hale getirilmelidir. Böylece ümmetin içindeki ayrılıkların temel nedeni olan mezhebi taassup ortadan kalkabilecek ve selef-i salîhîn döneminde olduğu gibi Müslümanlar birleşerek tekrar güçlü hale gelebilecektir. Bu araştırmada, Hasan el-Bennâ'nın fıkhi düşüncesi yaşadığı dönemin kendi dinamikleri dikkate alınarak ele alınmaya çalışılacaktır. Anahtar Kelimeler: Fıkıh, Hasan el-Bennâ, Delil, Kitab, Sünnet

Hasan al-Banna (1906-1949) lived in a period of transition, search and revolution that took place in every field, especially in social, cultural and legal fields, for the whole world and especially for the Islamic world. The determination of the fiqh and procedural views of Hasan al-Banna, who offered some solutions to the crises experienced by the Muslims in this period, is important in terms of examining the period. When the works of Bennâ as a scholar and man of action are examined, it is seen that his understanding of fiqh is on the axis of the thought of the predecessor of righteousness, but at the same time he supports this thought with an innovative and reformist approach. The fact that he expressed his views on the purpose of ensuring the unity of the ummah while explaining the procedural concepts, especially the ijmali evidence, shows that he developed different perspectives on the method while constructing the thought of fiqh. It can be said that he focused more on the Quran and the Sunnah, especially in his work called Fiqh Risalah. Because, according to him, the unity of Muslims from different races and sects against the understanding of the modern national state imposed by the West depends on these two essential proofs becoming more functional. Banna argued that the Quran can play an active role in institutionally transforming Muslims to the constitutional system. The position of the Quran in the hierarchy of evidence is correct according to him, but this evidence should be made functional in all areas of society, just like a constitution, in terms of applicability. In this way, sectarian bigotry, which is the main reason for the divisions within the ummah, will be eliminated and Muslims will be able to unite and become stronger again, as was the case in the time of the salaf-i salih. In this study, Hasan al-Banna's views and suggestions on the ijmali sources in his jurisprudence will be discussed by taking into account his own dynamics of the period in which he lived. Keywords: Fiqh, Hasan al-Banna, Source, Quran, Sunnah
Hasan al-Banna's fiqh thought between modernity and tradition
Keywords: Din